2018
DOI: 10.5455/njppp.2018.8.0619510062018
|View full text |Cite
|
Sign up to set email alerts
|

Night shift working and its impact on sleep quality, calorie intake, and serum thyroid stimulating hormone level among health-care workers in a tertiary hospital, Bengaluru

Abstract: Background: There are several health and social problems which are associated with shift work. This is mainly due to negative working environment and impairment of biological rhythms during the shift work. Aims and Objectives: The present study was designed to study the impact of night shift working on sleep quality, calorie intake, and serum thyroid stimulating hormone (TSH) level among health-care workers. Materials and Methods: Sleep quality, calorie intake, and serum TSH level were assessed by the Pittsbur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Comparably, in a retrospective study carried out on employees of a University hospital in Korea, Moon et al [26] demonstrated that night shift workers had significantly 0.303 mIU/L higher TSH levels, over a 5 year study period (2011-2015), compared to non-night shift workers after adjusting for age and employment department. In line with these results, a study on Indian healthcare professionals, including doctors, nurses, technicians and support staff, demonstrated that mean TSH values were significantly higher in night shift (3.11 ± 1.81 mIU/L) than day-shift workers (2.04 ± 0.8 mIU/L) [27].…”
Section: Healthcare Sectormentioning
confidence: 60%
See 3 more Smart Citations
“…Comparably, in a retrospective study carried out on employees of a University hospital in Korea, Moon et al [26] demonstrated that night shift workers had significantly 0.303 mIU/L higher TSH levels, over a 5 year study period (2011-2015), compared to non-night shift workers after adjusting for age and employment department. In line with these results, a study on Indian healthcare professionals, including doctors, nurses, technicians and support staff, demonstrated that mean TSH values were significantly higher in night shift (3.11 ± 1.81 mIU/L) than day-shift workers (2.04 ± 0.8 mIU/L) [27].…”
Section: Healthcare Sectormentioning
confidence: 60%
“…Overall, our search retrieved a total of 13 articles suitable for review ( Figure 1). Most of the reviewed studies assessed the association between shift-work and night-work and thyroid hormonal changes in different occupational settings [20][21][22][23][24][25][26][27][28][29] ( Table 1). Only a few publications focused on possible clinical adverse outcomes [26,[30][31][32].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 31 included studies represented 17 countries, with the greatest number of studies ( n = 15) conducted in the Asia-Pacific region [ 33 , 35 , 37 , 38 , 46 , [48] , [49] , [50] , [51] , [53] , [54] , [55] , [56] , [57] , [58] ], 12 from European countries [18,34,47,59–67], 3 from Turkey [36,68,69], and 1 from Israel [70]. Studies were published between 1979 and 2022, and most of them (n = 25) were of cross-sectional design, whereas 6 were observational studies.…”
Section: Resultsmentioning
confidence: 99%